PENGARUH KREDIBILITAS PENYULUH BADAN KEPENDUDUKAN KELUARGA BERENCANA (BKKBN) TERHADAP PENINGKATAN KESADARAN PENTINGNYA MENGATUR JARAK KELAHIRAN PADA MASYARAKAT KABUPATEN SIAK - Ayu Rosalia Dewi; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Siak is one of the cities with the highest population growth of Other District. Siak total population is constantly increasing. Since its inception in 2014 until December 2017, the increase reached 22.5% with the number of 112 425 inhabitants. In this case the birth rate would be an important role in determining the growth of the population, while it was to control the population increasing, the need for public awareness and outreach in this regard is the duty of the BKKBN. The problem of this study is how much influence the extension of Population Family Planning Agency (BKKBN) on the importance of birth spacing on Siak Regency society. The purpose of this study was to determine how much influence the extension of Population Family Planning Agency (BKKBN) on the importance of birth spacing on Siak Regency society. The method used in this research is descriptive quantitative. Total population of as many as 140 people Housewife (IRT), which actively participates in counseling BKKBN in Siak. The sample in this study amounted to 116 people were taken using sampling techniques according to Isaac and Michael. Measurement data using a Likert scale. Data analysis techniques used in this study is a simple linear regression. The results showed that a significant difference between the credibility of the communicator (X) to the communicant consciousness (Y) on the importance of birth spacing with significant values (sig.) Is 0.000 <0.05. Meanwhile, the proportion of the effects produced in this study is 0.534 or 53.4%. In other words, the credibility of the communicator (X) can affect consciousness communicant (Y) on the importance of spacing births is 53.4%.Keywords: Credibility, Communicators, Awareness, communicant, Birth